Accuracy of the concentration of morphine infusions prepared for patients in a neonatal intensive care unit. Issue 12 (22nd October 2013) - Aguado-Lorenzo, Virginia; Weeks, Kevin; Tunstell, Paul; Turnock, Karen; Watts, Timothy; Arenas-Lopez, Sara
Abstract : Objective: To investigate the accuracy of morphine infusions prepared for neonates in relation to the label strength and to identify the differences in deviation between infusions made in neonatal intensive care unit (NICU) and those dispensed ready-to-use from pharmacy. Methods: Unused portions of morphine solution for infusion were collected over a 6-weeks period and used to determine the concentration of the drug by high-performance liquid chromatography (HPLC). Results: A total of 19.2% of infusions prepared by nurses in the ward and 7.8% prepared in the pharmacy were outside the limit required by the British Pharmacopoeia (±7.5%). Moreover, a deviation in concentration of more than 20% was found in ward-prepared infusions, although this was caused by volume discrepancies of less than 0.2 mL. The frequency and magnitude of deviations found in infusions prepared in pharmacy was lower than in those prepared by NICU. The latter showed significantly higher number of out-of-specification samples (p=0.015); however, deviations from intended concentration occurred in both settings. Significant differences between pharmacy and NICU for volumes of less than 0.5 mL or for less than 1 mL were not identified probably due to small sample size, but statistical data show a trend for differences. Conclusions: Current practice of preparation of infusions from strengths intended for older children and adults involves dilution of small volumes in a syringe and leads to inaccuracy in the final concentration of infusions for neonatal use. We propose the implementation of standard concentrations for this patient group to effectively eliminate these errors.